2010
DOI: 10.2298/jsc090824119d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nitrogen-containing dispiroheterocycles using nitrilimines (II)

Abstract: A series of 1,2,4,9,10,12-hexaazadispiro[4.2.4.2]tetradeca-2,10-dienes (5a-j) was synthesized by the reaction of 1,4-cyclohexanedione oxime 3 with appropriate nitrilimines 2. The microanalysis and spectral data of the synthesized compounds are in full agreement with their molecular structure. The microbial features of some of the synthesized compounds were studied by a known method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…The identical pyrazolines protons at H 4 and H 4ʹʹ appear as a singlet at δ 3.61 ppm. This chemical shift value region is consistent with many similar reported structures, where the dipole molecules attack the olefinic linkages of diene system in a regioselective manner from two opposite faces . The 13 C‐NMR of 5ca reveals the pyrazoline methane carbons C 4/4ʹʹ as one signal at δ 58.9 ppm and the spiro‐carbons (C 3ʹ/5 ) and (C 1ʹ/5ʹʹ ) at δ 81.5 ppm.…”
Section: Resultssupporting
confidence: 89%
“…The identical pyrazolines protons at H 4 and H 4ʹʹ appear as a singlet at δ 3.61 ppm. This chemical shift value region is consistent with many similar reported structures, where the dipole molecules attack the olefinic linkages of diene system in a regioselective manner from two opposite faces . The 13 C‐NMR of 5ca reveals the pyrazoline methane carbons C 4/4ʹʹ as one signal at δ 58.9 ppm and the spiro‐carbons (C 3ʹ/5 ) and (C 1ʹ/5ʹʹ ) at δ 81.5 ppm.…”
Section: Resultssupporting
confidence: 89%
“…Literature has reported that 1,3-dipolar cycloaddition as one type of pericyclic reactions relating to six electrons could perform a versatile and efficient one-pot reaction to access five-membered heterocycles [84][85][86][87][88][89] particularly triazole derivatives starting from available oximes, hydrazones and hydrazonoyl halides [90][91][92]. The 1,3-dipolar cycloaddition of phenyl substituted hydrazonoyl chloride 59 with oxime 60 in the presence of excess triethylamine could generate triazole derivative 61 with broad antimicrobial spectrum (Scheme 22).…”
Section: Other Hydrazonesmentioning
confidence: 99%
“…Amidrazones synthesized from different hydrazonoyl halides were reported to react with α-haloesters in the presence of triethylamine as a base under reflux to afford 1,3,5-substituted 4,5-dihydro-1,2,4-triazin-6-ones 12 . Several studies, reported the formation and investigation of biological activities of some spiroheterocyclic compounds having triazole, tetrazine thiadiazole, thiadiazines, thiazolidinone and triazine moieties [13][14][15][16][17] . Recently, unknown dispiroheterocycles containing triazole and tetrazine moieties have been disclosed [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, reported the formation and investigation of biological activities of some spiroheterocyclic compounds having triazole, tetrazine thiadiazole, thiadiazines, thiazolidinone and triazine moieties [13][14][15][16][17] . Recently, unknown dispiroheterocycles containing triazole and tetrazine moieties have been disclosed [14][15][16][17] . Sulfonamide derivatives are known to exhibit various pharmacological properties such as antiangiogenic, anti-tumor, anti-inflammatory and anti-analgesic, anti-tubercular, anti-glaucoma, anti-HIV, cytotoxic, anti-microbial, anti-malarial agents 18 .…”
Section: Introductionmentioning
confidence: 99%